1992
DOI: 10.1104/pp.100.4.1948
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem II Core Phosphorylation Heterogeneity, Differential Herbicide Binding, and Regulation of Electron Transfer in Photosystem II Preparations from Spinach

Abstract: The effect of photosystem 11 core phosphorylation on the secondary quinone acceptor of photosystem 11 (QB) domain environment was analyzed by comparative herbicide-binding studies with photosystem 11 preparations from spinach (Spinacia oleracea L. leads to a decreased rate of PSII electron transfer at saturating light intensities (17-19). Further, it has been proposed that protein phosphorylation increases the ability of the QB pocket to bind herbicides (29), which may confer protection against photoinhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…4-6) is possibly due to a conformational change in the protein; insertion of the phosphate group alone cannot cause the observed change of 1-2 kDa in the size of the molecule. Secondly, Giardi et al (1992) have shown that the binding affinity of PSII herbicides to the QB niche decreased markedly in the PSII core populations with an increasing phosphorylation stage of the D1 protein. The loss of binding affinity was especially notable with i-Dinoseb and ioxynil (Giardi et al 1992), the herbicides which most efficiently suppressed the degradation of D1 protein under physiological light conditions (Jansen et al 1993).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4-6) is possibly due to a conformational change in the protein; insertion of the phosphate group alone cannot cause the observed change of 1-2 kDa in the size of the molecule. Secondly, Giardi et al (1992) have shown that the binding affinity of PSII herbicides to the QB niche decreased markedly in the PSII core populations with an increasing phosphorylation stage of the D1 protein. The loss of binding affinity was especially notable with i-Dinoseb and ioxynil (Giardi et al 1992), the herbicides which most efficiently suppressed the degradation of D1 protein under physiological light conditions (Jansen et al 1993).…”
Section: Discussionmentioning
confidence: 98%
“…Secondly, Giardi et al (1992) have shown that the binding affinity of PSII herbicides to the QB niche decreased markedly in the PSII core populations with an increasing phosphorylation stage of the D1 protein. The loss of binding affinity was especially notable with i-Dinoseb and ioxynil (Giardi et al 1992), the herbicides which most efficiently suppressed the degradation of D1 protein under physiological light conditions (Jansen et al 1993). These results suggest that the phosphorylation of the N-terminal domain may influence the orientation of those domains in the D1 protein that are involved in the formation of the QB niche.…”
Section: Discussionmentioning
confidence: 98%
“…The light-harvesting complexes were collected as a green band at the position of 0.4 M sucrose while the PSII core preparation was recovered as a pellet at the bottom of the tube. Alternatively, the PSII membranes were gently solubilized with 0.3% DM and applied to an isoelectrofocusing bed of Ultrodex gel (pH range 3.5-5; LKB, Bromma, Sweden) to separate light-harvesting complex protein (LHCP) from the remaining PSII cores (Giardi et al 1992). The gel bed was cut into sections 1 cm wide and the polypeptide profile was assessed by SDS-PAGE and immunoblotting as described by Barbato et al (1991).…”
Section: Methodsmentioning
confidence: 99%
“…Herbicide binding was performed on isolated thylakoids as previously reported, using radiolabelled ioxynil (3.3" 1011 Bq.mmol-i; Giardi et al 1992;Giardi 1993b), a kind gift from May and Baker Ltd. (London, UK). The QB content, the dissociation constant and the number of herbicide-binding sites were obtained from double reciprocal plots of free versus bound herbicide concentration.…”
Section: Methodsmentioning
confidence: 99%
“…These PSII cores show different QB pocket functioning with respect to plastoquinone (PQ) binding (Giardi et al 1992a). In the present work, the effect of photoinhibitory conditions on the distribution of phosphorylated PSII core populations is studied.…”
Section: Introductionmentioning
confidence: 99%